Looking for "justice" in all the wrong places. - Amarasingam, Edited by Amarnath; Bass, Daniel (Sri Lanka: The Struggle for Peace in the Aftermath of War, 2017)
Even though Sri Lanka's protracted civil war came to a bloody conclusion in May 2009, prospects for a sustainable peace remain uncertain. The Sri Lankan army is no longer waging military campaigns and the separatist Liberation Tigers of Tamil Eelam (LTTE) are no longer carrying out political assassinations and suicide attacks, yet structural violence continues, and has arguably intensified since the war's end. Anti-Tamil discrimination, anti-Muslim violence, and Sinhala Buddhist majoritarianism all increased in the war's aftermath, as President Mahinda Rajapakse's government invoked its military victory over the LTTE to silence any opposition. The election of Maithripala Sirisena as president in January 2015 began to alleviate some of the worst of these post-war abuses of power, but many long-term problems will take longer to solve. This book brings together scholars in the fields of anthropology, sociology, history, law, religious studies and diaspora studies to critically engage issues such as post-war development, constitutional reform, ethnic and religious identity, transnational activism, and transitional justice. Through an interdisciplinary approach to post-war Sri Lanka, this volume examines the intractable and complex issues that continue to plague this war-torn island. , Even though Sri Lanka's protracted civil war came to a bloody conclusion in May 2009, prospects for a sustainable peace remain uncertain. The Sri Lankan army is no longer waging military campaigns and the separatist Liberation Tigers of Tamil Eelam (LTTE) are no longer carrying out political assassinations and suicide attacks, yet structural violence continues, and has arguably intensified since the war's end. Anti-Tamil discrimination, anti-Muslim violence, and Sinhala Buddhist majoritarianism all increased in the war's aftermath, as President Mahinda Rajapakse's government invoked its military victory over the LTTE to silence any opposition. The election of Maithripala Sirisena as president in January 2015 began to alleviate some of the worst of these post-war abuses of power, but many long-term problems will take longer to solve. This book brings together scholars in the fields of anthropology, sociology, history, law, religious studies and diaspora studies to critically engage issues such as post-war development, constitutional reform, ethnic and religious identity, transnational activism, and transitional justice. Through an interdisciplinary approach to post-war Sri Lanka, this volume examines the intractable and complex issues that continue to plague this war-torn island.
Keywords: Sujith Xavier